Comprehensive analysis of MET mutations in NSCLC patients in a real-world setting. (July 2022) - Ai, Xinghao; Yu, Yongfeng; Zhao, Jun; Sheng, Wang; Bai, Jing; Fan, Zaiwen; Liu, Xuemei; Ji, Wenxiang; Chen, Rongrong; Lu, Shun
Background: Aberrant mesenchymal–epithelial transition/hepatocyte growth factor (MET/HGF) regulation presented in a wide variety of human cancers. MET exon 14 skipping, copy number gain (CNG), and kinase domain mutations/arrangements were associated with increased MET activity, and considered to be oncogenic drivers of non-small cell lung cancers (NSCLCs). Methods: We retrospectively analyzed 564 patients with MET alterations. MET alterations were classified into structural mutations or small mutations. MET CNG, exon 14 skipping, gain of function (GOF) mutations, and kinase domain rearrangement were defined as actionable mutations. Results: Six hundred thirty-two MET mutations were identified including 199 CNG, 117 exon 14 skipping, 12 GOF mutations, and 2 actionable fusions. Higher percentage of MET structural alterations (CNG + fusion) were detected in advanced NSCLC patients. Moreover, MET CNG was enriched while exon 14 skipping was rare in epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKI)-treated advanced NSCLC patients. Ten of the 12 MET GOF mutations were also in EGFR-TKI-treated patients. Fifteen (68.1%) of the 22 patients treated with crizotinib or savolitinib had a partial response. Interestingly, one patient had a great response to savolitinib with a novel MET exon 14 skipping mutation identified after failure of immune-checkpoint inhibitor. Conclusions: Half of the MET alterations were actionable mutations. MET CNG, exon 14 skipping and GOF mutations had different distribution in different clinical scenario but all defined a molecular subgroup of NSCLCs for which MET inhibition was active.